2009
DOI: 10.1182/blood-2008-09-181024
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of B-lymphoid kinase in cutaneous T-cell lymphoma

Abstract: IntroductionCutaneous T-cell lymphomas (CTCL) are the most frequent primary lymphomas of the skin, with mycosis fungoides (MF) being the most prevalent clinical form. 1 In early disease stages, which can last several years, MF presents as flat erythematous skin patches resembling inflammatory diseases such as allergic contact dermatitis, eczema, or psoriasis. In later stages, MF lesions gradually form plaques and overt tumors and may disseminate to lymph nodes and internal organs. The early skin lesions contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 49 publications
(77 reference statements)
6
54
0
2
Order By: Relevance
“…TOX (Thymocyte selectionassociated high mobility group box) and EVA1 (Epithelial C-like antigen 1) are usually expressed in thymocyte development, but are subsequently downregulated in mature T cells, 25,26 while BLK (B-lymphoid kinase) and POU2AF are usually specific to B cells and should not be expressed in T cells. 27,28 PLS3 (Plastin 3) is an actin binding protein, which is also normally not expressed in T cells. 6,29 Our RT-PCR analysis confirms that BLK, POU2AF, TOX, EVA1, and PLS3 are expressed in CTCL lesional skin biopsies (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TOX (Thymocyte selectionassociated high mobility group box) and EVA1 (Epithelial C-like antigen 1) are usually expressed in thymocyte development, but are subsequently downregulated in mature T cells, 25,26 while BLK (B-lymphoid kinase) and POU2AF are usually specific to B cells and should not be expressed in T cells. 27,28 PLS3 (Plastin 3) is an actin binding protein, which is also normally not expressed in T cells. 6,29 Our RT-PCR analysis confirms that BLK, POU2AF, TOX, EVA1, and PLS3 are expressed in CTCL lesional skin biopsies (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…27 Importantly, BLK is constitutively active in malignant T cells and appears to be a bona fide oncogene which drives malignant T cell proliferation in vitro and tumor formation in vivo. 27,51 In addition, recent translational experimental work revealed that TOX expression, which is usually silenced in mature T cells, can be used as a robust prognostic and diagnostic marker for MF and SS, 52,53 while PLS3 actin binding protein, which is usually not expressed in T cells is consistently expressed in CTCL. 6,29,54,55 A growing body of literature documents that ectopic expression of these genes in CTCL is not a mere indication of deregulated cellular processes, but an important mechanism of tumorigenesis and cancer progression.…”
Section: E970025-4 Volume 3 Issue 11 Oncoimmunologymentioning
confidence: 99%
“…Cyclin upregulation, including cyclinD1, and loss of RB1 have also been described [94]. As gene-expression profiling and nextgeneration sequencing technologies are used, additional pathogenic pathways, including those involving transcription factors regulating T-cell differentiation [35,36], c-MYC [95,96], RAS/RAF/MEK signaling [97], among others [90,98], may be identified in subsets of CTCL.…”
Section: Immunopathogenesismentioning
confidence: 99%
“…Total RNA was isolated using RNeasy Mini Kit (Qiagen, Ballerup, Denmark) according to the manufacturer's instructions and reverse transcriptase-PCR was performed as described elsewhere 17 (all reagents were from Invitrogen, Paisley, UK; Taq polymerase is from New England Biolabs, Danvers, MA, USA). Primers (Supplementary Figure 1) were designed with Primer3, v 0.4.0 software (Duke-NUS Graduate Medical School, Singapore) 18 and synthesized by Eurofins MWG GmbH (Martinsried, Germany).…”
Section: Rna Isolation and Reverse Transcriptase-pcrmentioning
confidence: 99%
“…17 Samples were analyzed on a FACSCalibur using CellQuestPro software (Becton Dickinson, Brøndby, Denmark).…”
Section: Flow Cytometrymentioning
confidence: 99%